AMP Advances in Mathematical Physics 1687-9139 1687-9120 Hindawi Publishing Corporation 10.1155/2015/864792 864792 Research Article Jordan Isomorphisms on Nest Subalgebras Yang Aili Cleaver Gerald College of Science Xi’an University of Science and Technology Xi’an 710054 China xust.edu.cn 2015 1942015 2015 05 12 2014 05 02 2015 1942015 2015 Copyright © 2015 Aili Yang. This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

This paper is devoted to the study of Jordan isomorphisms on nest subalgebras of factor von Neumann algebras. It is shown that every Jordan isomorphism ϕ between the two nest subalgebras alg M β and alg M γ is either an isomorphism or an anti-isomorphism.

1. Introduction

Let A and B be two associative algebras. A Jordan isomorphism ϕ from A onto B is a bijective linear map such that ϕ ( T 2 ) = ϕ ( T ) 2 for every T A . Obviously, isomorphisms and anti-isomorphisms are basic examples of Jordan isomorphisms. Jordan isomorphisms have been studied by many authors for various rings and algebras (see ). The standard problem is to determine whether a Jordan isomorphism is either an isomorphism or an anti-isomorphism. Using linear algebraic techniques, Molnár and Šemrl  proved that automorphisms and antiautomorphisms are the only linear Jordan automorphisms of T n ( F ) , n 2 , where F is a field with at least three elements. Later, Beidar et al.  generalized this result and proved that every linear Jordan isomorphisms of T n ( C ) , n 2 , onto an arbitrary algebra over C , is either an isomorphism or an anti-isomorphism, where C is a 2-torsionfree commutative ring which is connected, that is, a ring in which the only idempotents are 0 and 1. Recently, Zhang  proved that every Jordan isomorphism ϕ between two nest algebras alg β and alg γ is either an isomorphism or an anti-isomorphism. The same result was concluded in  for Jordan isomorphisms on nest algebras. The motivation for this paper is the work by Zhang. The aim of the present paper is to characterize Jordan isomorphisms of nest subalgebras.

In fact, the characterization of Jordan isomorphisms is closely related to isometric problems (see ). However, Jordan algebras or structures are related to vertex (operator) algebras or superalgebras and to representations of Kac-Moody and Virasoro algebras . Note that the vertex operators of string theory also give reps of Lie algebras and Kac-Moody and Virasoro algebras (both infinite dimensional Lie algebras) as well as reps of the Fischer-Griess Monster group algebra. Jordan algebras or structures are also related to QFT, CFT, SCAs, and WZW models . Another paper  about M -theory with J3(O) and F4 makes use of the algebraic Kostant-Dirac operator, and a variant of this operator also appears on page 12 of a paper  about a gerbe based approach to supersymmetric WZW models (gerbes are useful in string theory; e.g., gerbes help in illuminating the geometry of mirror symmetry of CY threefolds, help in giving a noncommutative description of D -branes in the presence of topologically nontrivial background fields, and provide a geometric way to unify properties of p -form fields with gauge symmetries, etc.). There is more about how Jordan structures are involved with physics . This paper studies the structure of Jordan isomorphisms of nest subalgebras. Our main result is that every Jordan isomorphism of nest subalgebras is either an isomorphism or an anti-isomorphism.

Now, let us introduce some notions and concepts that will be used later. Let M be a von Neumann algebra acting on a separable Hilbert space H . A nest β in M is totally a family of (self-adjoint) projections in M which is closed in the strong operator topology and included 0 and I . The nest subalgebra of M associated with a nest β , denoted by alg M β , is the set alg M β = { T M : P T P = T P    for    all    P β } . The diagonal D M ( β ) of a nest subalgebra alg M β is the von Neumann subalgebra ( alg M β ) ( alg M β ) * . Let R M ( β ) denote the norm closed algebra generated by { P T ( I - P ) : T M , P β } . It is clear that R M ( β ) is a norm closed ideal of the nest subalgebra alg M β . If M is a factor von Neumann algebra, it follows from  that D M ( β ) + R M ( β ) is weakly dense in alg M β . When M = B ( H ) , alg M β is called a nest algebra and is denoted by alg β . As a notational convenience, if P is an idempotent, we let P denote I - P throughout this paper.

We refer the readers to  for background information about von Neumann algebras and to  for the theory of nest algebras and nest subalgebras.

2. Main Result

The following theorem is our main result.

Theorem 1.

Let a l g M β , a l g M γ be two nontrivial subalgebras in factor von Neumann algebra M , and let ϕ : a l g M β a l g M γ be a Jordan isomorphism. Then, ϕ is either an isomorphism or an anti-isomorphism.

The proof is purely algebraic and will be organized in a series of lemmas. As a notational convenience, throughout this paper, we assume that β and γ are nontrivial nests in a factor von Neumann algebra M and that ϕ : a l g M β a l g M γ is a Jordan isomorphism.

Lemma 2.

Let β be a nest in factor von Neumann algebra M , and then, for X , Y M , X ( a l g M β ) Y = 0 if and only if there exists a projection P β such that X = X P , Y = P Y .

Proof.

It is clear that if there exists a projection P β such that X = X P , Y = P Y , then X ( alg M β ) Y = 0 .

Clearly, let K be the closure of the space ( alg M β ) Y H , and let P be the projection onto K . Then, P M and P T P = 0 for all T alg M β , and so P β . It is clear that X P = 0 , P Y = 0 . Thus, X = X P , Y = P Y . The proof is complete.

Lemma 3.

ϕ ( I ) = I , and, for any A , B , T a l g M β , the following are equivalent:

ϕ ( A 2 ) = ϕ ( A ) 2 ;

ϕ ( A B + B A ) = ϕ ( A ) ϕ ( B ) + ϕ ( B ) ϕ ( A ) ;

ϕ ( A B A ) = ϕ ( A ) ϕ ( B ) ϕ ( A ) ;

ϕ ( A B T + T B A ) = ϕ ( A ) ϕ ( B ) ϕ ( T ) + ϕ ( T ) ϕ ( B ) ϕ ( A ) .

Proof.

As ( a ) ( b ) , let X = A + B , and then, by (a), we have (1) φ X 2 = ϕ A 2 + ϕ A B + B A + ϕ B 2 = ϕ A + ϕ B 2 . This shows that (b) is established.

As ( b ) ( c ) , by (b), (2) 2 ϕ A B A = ϕ [ ( A B + B A ) A + A ( A B + B A ) ] - ϕ ( A 2 B + B A 2 ) = [ ϕ ( A ) ϕ ( B ) + ϕ ( B ) ϕ ( A ) ] ϕ ( A ) = + ϕ A ϕ A ϕ B + ϕ B ϕ A = - ϕ A 2 ϕ ( B ) - ϕ ( B ) ϕ A 2 = 2 ϕ ( A ) ϕ ( B ) ϕ ( A ) .

As ( c ) ( d ) , (3) ϕ A B T + T B A = ϕ A + T B A + T - ϕ A B A - ϕ T B T = ϕ A + ϕ T ϕ B ϕ A + ϕ T = - ϕ ( A ) ϕ ( B ) ϕ ( A ) - ϕ T ϕ B ϕ T = ϕ ( A ) ϕ ( B ) ϕ ( T ) + ϕ T ϕ B ϕ A .

Taking B = I in (b), we get (4) 2 ϕ ( A ) = ϕ ( A ) ϕ ( I ) + ϕ ( I ) ϕ ( A ) . Multiplying the above equation on both sides by ϕ ( I ) and noticing that ϕ ( I ) 2 = ϕ ( I ) , we have (5) ϕ I ϕ A = ϕ I ϕ A ϕ I , ϕ ( A ) ϕ ( I ) = ϕ ( I ) ϕ ( A ) ϕ ( I ) . Thus, for any A alg M β , ϕ ( A ) ϕ ( I ) = ϕ ( I ) ϕ ( A ) . It follows from M ( alg M β ) = C I that ϕ ( I ) = I . Hence, (a)–(d) are equivalent.

Lemma 4.

If P β / { 0 , I } , then, for all T , S a l g M β , one has (6) ϕ ( P ) ϕ ( T ) ϕ ( P ) ϕ ( S ) ϕ ( P ) = 0 ; ϕ ( P ) ϕ ( S ) ϕ ( P ) ϕ ( T ) ϕ ( P ) = 0 ; ϕ ( P ) ϕ ( S ) ϕ ( P ) ϕ ( T ) ϕ ( P ) = 0 ; ϕ ( P ) ϕ ( T ) ϕ ( P ) ϕ ( S ) ϕ ( P ) = 0 .

Proof.

By Lemma 3(b), for all T alg M β , (7) ϕ ( P T P ) = ϕ ( P ) ϕ ( T ) ϕ ( P ) + ϕ ( P ) ϕ ( T ) ϕ ( P ) . Let S alg M β , and then (8) ϕ P ϕ T ϕ P ϕ S ϕ P + ϕ ( P ) ϕ ( T ) ϕ ( P ) ϕ ( S ) ϕ ( P ) + ϕ P ϕ S ϕ P ϕ T ϕ P + ϕ ( P ) ϕ ( S ) ϕ ( P ) ϕ ( T ) ϕ ( P ) = ϕ ( P ) ϕ ( T ) ϕ ( P ) + ϕ ( P ) ϕ ( T ) ϕ ( P ) · ϕ ( P ) ϕ ( S ) ϕ ( P ) + ϕ ( P ) ϕ ( S ) ϕ ( P ) + ϕ P ϕ S ϕ P + ϕ P ϕ S ϕ P · ϕ P ϕ T ϕ P + ϕ P ϕ T ϕ P = ϕ ( P T P ) ϕ ( P S P ) + ϕ ( P S P ) ϕ ( P T P ) = 0 . This implies that (9) ϕ P ϕ T ϕ P ϕ S ϕ P + ϕ P ϕ S ϕ P ϕ T ϕ P = 0 , ϕ P ϕ T ϕ P ϕ S ϕ P + ϕ P ϕ S ϕ P ϕ T ϕ P = 0 . By (9), (10) ϕ - 1 ϕ ( P ) ϕ ( T ) ϕ ( P ) ϕ ( S ) ϕ ( P ) + ϕ ( P ) ϕ ( S ) ϕ ( P ) ϕ ( T ) ϕ ( P ) = ϕ - 1 ϕ P ϕ T ϕ P ϕ - 1 ϕ P ϕ S ϕ P + ϕ - 1 ϕ P ϕ S ϕ P ϕ - 1 ϕ P ϕ T ϕ P = P T P - ϕ - 1 ϕ P ϕ T ϕ P · P S P - ϕ - 1 ϕ P ϕ S ϕ P + P S P - ϕ - 1 ϕ P ϕ S ϕ P · P T P - ϕ - 1 ϕ P ϕ T ϕ P = ϕ - 1 ϕ ( P ) ϕ ( T ) ϕ ( P ) ϕ ( S ) ϕ ( P ) + ϕ ( P ) ϕ ( S ) ϕ ( P ) ϕ ( T ) ϕ ( P ) + P A P = - ϕ - 1 ϕ ( P ) ϕ ( T ) ϕ ( P ) ϕ ( S ) ϕ ( P ) + ϕ ( P ) ϕ ( S ) ϕ ( P ) ϕ ( T ) ϕ ( P ) + P A P , where (11) A = - P T P ϕ P ϕ S ϕ P ϕ - 1 ϕ P ϕ T ϕ P = - + ϕ - 1 ϕ P ϕ T ϕ P P S P = - + ϕ - 1 ϕ P ϕ S ϕ P P T P = - + P S P ϕ - 1 ϕ P ϕ T ϕ P . Clearly, A alg M β . Thus, by the above equation, we have (12) ϕ P ϕ T ϕ P ϕ S ϕ P + ϕ ( P ) ϕ ( S ) ϕ ( P ) ϕ ( T ) ϕ ( P ) = 1 2 ϕ P A P = 1 2 [ ϕ ( P ) ϕ ( A ) ϕ ( P ) + ϕ ( P ) ϕ ( A ) ϕ ( P ) ] . This shows that, for any T , S alg M β , (13) ϕ P ϕ T ϕ P ϕ S ϕ P = ϕ ( P ) ϕ ( S ) ϕ ( P ) ϕ ( T ) ϕ ( P ) = 0 .

Lemma 5.

For any T a l g M β and any projection P β , either ϕ ( P T P ) = ϕ ( P ) ϕ ( T ) ϕ ( P ) or ϕ ( P T P ) = ϕ ( P ) ϕ ( T ) ϕ ( P ) .

Proof.

If P = 0 or P = I , the result is clear. Suppose that P β / { 0 , I } . Let (14) A = ϕ P ϕ T ϕ P , B = ϕ ( P ) ϕ ( T ) ϕ ( P ) . Then, by Lemma 4, for any X alg M γ , (15) ϕ ( P ) X A = ϕ ( P ) X B = 0 . By Lemma 2 and (15), there exists a projection P 1 γ such that (16) ϕ ( P ) = ϕ ( P ) P 1 ; (17) A = P 1 A . There exists a projection P 2 γ such that (18) ϕ ( P ) = ϕ ( P ) P 2 ; (19) B = P 2 B . By (16) and (18), we have (20) ϕ ( P ) P 1 + ϕ ( P ) P 2 = ϕ ( I ) = I . Multiplying the above equation on both sides from the right side by P 1 P 2 , we get P 1 P 2 = 0 . If A 0 , then by (17)   P 1 0 . So, P 2 = 0 . Hence, by (19), B = 0 . Similarly, if B 0 , then A = 0 . This implies that A = 0 or B = 0 . From the fact that ϕ ( P T P ) = A + B , for all T alg M β , one of the following is set up: (21) ϕ P T P = ϕ P ϕ T ϕ P , ϕ ( P T P ) = ϕ ( P ) ϕ ( T ) ϕ ( P ) . Since M is factor, then there exists a partial isometry operator V M such that V = P V P , thus, V alg M β . Therefore, either ϕ ( V ) = ϕ ( P ) ϕ ( V ) ϕ ( P ) or ϕ ( V ) = ϕ ( P ) ϕ ( V ) ϕ ( P ) . Suppose ϕ ( V ) = ϕ ( P ) ϕ ( V ) ϕ ( P ) , if there exists S alg M β such that ϕ ( P S P ) ϕ ( P ) ϕ ( S ) ϕ ( P ) , then ϕ ( P S P ) = ϕ ( P ) ϕ ( S ) ϕ ( P ) . On the other hand, one of the following is set up: (22) ϕ V + P S P = ϕ P ϕ V + S ϕ P , ϕ ( V + P S P ) = ϕ ( P ) ϕ ( V + S ) ϕ ( P ) . And ϕ ( V ) = ϕ ( P ) ϕ ( V ) ϕ ( P ) , ϕ ( P S P ) ϕ ( P ) ϕ ( S ) ϕ ( P ) ; hence, (23) ϕ ( V + P S P ) = ϕ ( P ) ϕ ( V + S ) ϕ ( P ) . So, ϕ ( V ) = ϕ ( P ) ϕ ( V ) ϕ ( P ) = ϕ ( P ) ϕ ( V ) ϕ ( P ) . This shows that ϕ ( V ) = 0 ; thus, V = 0 . A contradiction. In conclusion, for any T alg M β , we have ϕ ( P T P ) = ϕ ( P ) ϕ ( T ) ϕ ( P ) . Similarly, suppose that ϕ ( V ) = ϕ ( P ) ϕ ( V ) ϕ ( P ) , and then, for any T alg M β , we have ϕ ( P T P ) = ϕ ( P ) ϕ ( T ) ϕ ( P ) . Consequently, for any T alg M β and any projection P β , either ϕ ( P T P ) = ϕ ( P ) ϕ ( T ) ϕ ( P ) or ϕ ( P T P ) = ϕ ( P ) ϕ ( T ) ϕ ( P ) .

Proof of Theorem <xref ref-type="statement" rid="thm2.1">1</xref>.

By Lemma 5, if, for any T alg M β , (24) ϕ ( P T P ) = ϕ ( P ) ϕ ( T ) ϕ ( P ) , let A alg M β , and then (25) ϕ P A P T P = ϕ ( P ) ϕ ( P A P ) ϕ ( P T P ) ϕ ( P ) + ϕ ( P ) ϕ ( P T P ) ϕ ( P A P ) ϕ ( P ) . Thus, for all T , A alg M β , we have (26) ϕ ( P A P T P ) = ϕ ( P A P ) ϕ ( P T P ) . Clearly, (27) ϕ ( P A P P T P ) = ϕ ( P A P ) ϕ ( P T P ) = 0 , ϕ ( P A P P T P ) = ϕ ( P A P ) ϕ ( P T P ) = 0 . By (26)-(27), for all A , T alg M β , we have (28) ϕ ( A P T P ) = ϕ ( A ) ϕ ( P T P ) . Similar to the proof of (28), for any A , T alg M β , (29) ϕ ( P T P A ) = ϕ ( P T P ) ϕ ( A ) . Let A , B alg M β , and by (28), for any T alg M β , (30) ϕ A B P T P = ϕ A B ϕ P T P = ϕ A ϕ B P T P = ϕ ( A ) ϕ ( B ) ϕ ( P T P ) . Thus, for all A , B alg M β , we have (31) [ ϕ ( A B ) - ϕ ( A ) ϕ ( B ) ] ϕ ( P ) alg M γ ϕ ( P ) = 0 . Similarly, by (29), (32) ϕ ( P ) alg M γ ϕ ( P ) [ ϕ ( A B ) - ϕ ( A ) ϕ ( B ) ] = 0 . By the above two equations and Lemma 2, there exists a projection Q 1 γ such that (33) ϕ A B - ϕ A ϕ B ϕ P = [ ϕ ( A B ) - ϕ ( A ) ϕ ( B ) ] ϕ ( P ) Q 1 ; (34) ϕ ( P ) = Q 1 ϕ ( P ) . And there exists a projection Q 2 γ such that (35) ϕ ( P ) = ϕ ( P ) Q 2 ; (36) ϕ P ϕ A B - ϕ A ϕ B = Q 2 ϕ ( P ) [ ϕ ( A B ) - ϕ ( A ) ϕ ( B ) ] . Since ϕ is a Jordan isomorphism and ϕ ( P T P ) = ϕ ( P ) ϕ ( T ) ϕ ( P ) , then, for any T alg M β , we have (37) ϕ ( P ) ϕ ( T ) ϕ ( P ) = 0 . Especially, ϕ ( P ) Q 1 ϕ ( P ) = 0 ; that is, ϕ ( P ) Q 1 ϕ ( P ) = ϕ ( P ) Q 1 . Thus, by formula (34), we have (38) ϕ ( P ) Q 1 = Q 1 ϕ ( P ) = 0 . This implies that Q 1 [ ϕ ( P ) ] = 0 , where [ ϕ ( P ) ] is an orthogonal projection onto ϕ ( P ) H . Since P is a nontrivial projection, then [ ϕ ( P ) ] 0 , thus, Q 1 = 0 . Therefore, by (33), (39) [ ϕ ( A B ) - ϕ ( A ) ϕ ( B ) ] ϕ ( P ) = 0 . By (35) and similar discussion, we get (40) ϕ ( P ) Q 2 = Q 2 ϕ ( P ) = 0 . This shows that [ ϕ ( P ) ] Q 2 = 0 ; thus, Q 2 = 0 . So, by (36), (41) ϕ ( P ) [ ϕ ( A B ) - ϕ ( A ) ϕ ( B ) ] = 0 . In addition, by Lemma 3(c), we have (42) ϕ P ϕ A B ϕ P = ϕ P A P B P + ϕ P A P B P = ϕ ( P A P ) ϕ ( P B P ) + ϕ ( P A P ) ϕ ( P B P ) = ϕ P ϕ A ϕ P ϕ B ϕ P + ϕ ( P ) ϕ ( A ) ϕ ( P ) ϕ ( B ) ϕ ( P ) . Thus, for any A , B alg M β , we have (43) ϕ ( P ) [ ϕ ( A B ) - ϕ ( A ) ϕ ( B ) ] ϕ ( P ) = 0 . By (39) and (41), for all A , B alg M β , we have ϕ ( A B ) = ϕ ( A ) ϕ ( B ) . Hence, ϕ is an isomorphism.

If for any T alg M β , we have ϕ ( P T P ) = ϕ ( P ) ϕ ( T ) ϕ ( P ) , then, for any X alg M β , we define ψ ( X ) = ϕ ( J X * J ) , where J is a conjugate linear involution operator defined in Lemma 2.3 of . It is not difficult to verify that ψ : alg M β alg M γ is a Jordan isomorphism and, for any projection Q β / { 0 , I } , we have (44) ψ ( Q X Q ) = ψ ( Q ) ψ ( X ) ψ ( Q ) . Thus, from the above discussion, ψ is an isomorphism. Consequently, ϕ is an anti-isomorphism.

By Lemma 5, for all T alg M β , one of the following holds: (45) ϕ ( P T P ) = ϕ ( P ) ϕ ( T ) ϕ ( P ) or ϕ ( P T P ) = ϕ ( P ) ϕ ( T ) ϕ ( P ) . If ϕ ( P T P ) = ϕ ( P ) ϕ ( T ) ϕ ( P ) , then Lemma 3(c) and the fact that B P = P B P imply that (46) ϕ A B ϕ P T P = ϕ A B P T P = ϕ A ϕ B P T P = ϕ ( A ) ϕ ( B ) ϕ ( P T P ) for all A , B alg M β . Hence, for all A , B alg M β , we have (47) [ ϕ ( A B ) - ϕ ( A ) ϕ ( B ) ] ϕ ( P ) alg M γ ϕ ( P ) = 0 . Similarly, it follows from Lemma 3(c) and P A = P A P that, for all A , B alg M β , we have (48) ϕ ( P ) alg M γ ϕ ( P ) [ ϕ ( A B ) - ϕ ( A ) ϕ ( B ) ] = 0 . By (47), (48), and Lemma 2, there exists a projection Q 1 , Q 2 γ such that (49) ϕ A B - ϕ A ϕ B ϕ P = [ ϕ ( A B ) - ϕ ( A ) ϕ ( B ) ] ϕ ( P ) Q 1 ; (50) ϕ P = Q 1 ϕ P ; (51) ϕ ( P ) = ϕ ( P ) Q 2 ; (52) ϕ P ϕ A B - ϕ A ϕ B = Q 2 ϕ ( P ) [ ϕ ( A B ) - ϕ ( A ) ϕ ( B ) ] . Since ϕ ( P T P ) = ϕ ( P ) ϕ ( T ) ϕ ( P ) , we have ϕ ( P ) ϕ ( T ) ϕ ( P ) = 0 for all T alg M β . Let ϕ P M , and [ ϕ ( P ) ] denote the orthogonal projection from H to ϕ ( P ) H . In particular, ϕ ( P ) Q 1 ϕ ( P ) = 0 ; that is, ϕ ( P ) Q 1 ϕ ( P ) = ϕ ( P ) Q 1 . Thus, by formula (50), (53) ϕ ( P ) Q 1 = Q 1 ϕ ( P ) = 0 . This shows that Q 1 [ ϕ ( P ) ] = 0 . Since P is a nontrivial projection, then [ ϕ ( P ) ] 0 , so Q 1 = 0 . By (49), (54) [ ϕ ( A B ) - ϕ ( A ) ϕ ( B ) ] ϕ ( P ) = 0 . In similar discussion, we have ϕ ( P ) Q 2 = Q 2 ϕ ( P ) = 0 . This shows that [ ϕ ( P ) ] Q 2 = 0 , so Q 2 = 0 . Thus, by (52), (55) ϕ ( P ) [ ϕ ( A B ) - ϕ ( A ) ϕ ( B ) ] = 0 . Because P B P P A P = 0 , by Lemma 3, we have (56) ϕ P A P B P = ϕ P B P P A P = ϕ P B P ϕ P A P = ϕ ( P B P ) ϕ ( P A P ) for all A , B alg M β . Since P B P P A P = 0 , similarly, (57) ϕ ( P A P B P ) = ϕ ( P A P ) ϕ ( P B P ) . By (56), (57), and Lemma 4, (58) ϕ P ϕ A B ϕ P = ϕ P A P B P + ϕ P A P B P = ϕ ( P A P ) ϕ ( P B P ) + ϕ ( P A P ) ϕ ( P B P ) = ϕ P ϕ A ϕ P ϕ B ϕ P + ϕ ( P ) ϕ ( A ) ϕ ( P ) ϕ ( B ) ϕ ( P ) = ϕ ( P ) ϕ ( A ) ϕ ( B ) ϕ ( P ) . Thus, for all A , B alg M β , we have (59) ϕ ( P ) [ ϕ ( A B ) - ϕ ( A ) ϕ ( B ) ] ϕ ( P ) = 0 . By (54), (55), and (59), we have ϕ ( A B ) = ϕ ( A ) ϕ ( B ) for any A , B alg M β . Similarly, ϕ ( A B ) = ϕ ( B ) ϕ ( A ) .

Consequently, ϕ is either an isomorphism or anti-isomorphism.

Conflict of Interests

The author declares that there is no conflict of interests regarding the publication of this paper.

Acknowledgments

The author wishes to thank the referees for their time and comments. He thanks Dr. Yongjian Xie from the College of Mathematics and Information Science, Shaanxi Normal University, Xi’an, China. This paper is supported by the Fundamental Research Funds for the Central Universities (Grant no. GK201503017).

Herstein I. N. Jordan homomorphisms Transactions of the American Mathematical Society 1956 81 331 341 MR0076751 10.1090/S0002-9947-1956-0076751-6 Baxter W. E. Martindale W. S. Jordan homomorphisms of semiprime rings Journal of Algebra 1979 56 2 457 471 2-s2.0-0001339712 10.1016/0021-8693(79)90349-1 MR528587 Brešar M. Jordan mappings of semiprime rings Bulletin of the Australian Mathematical Society 1991 44 2 233 238 MR1126361 10.1017/s000497270002966x Brešar M. Jordan mappings of semiprime rings Journal of Algebra 1989 127 1 218 228 10.1016/0021-8693(89)90285-8 MR1029414 2-s2.0-0001470552 Wong T.-L. Jordan isomorphisms of triangular rings Proceedings of the American Mathematical Society 2005 133 11 3381 3388 2-s2.0-27844486429 MR2161163 10.1090/s0002-9939-05-07989-x Molnár L. Šemrl P. Some linear preserver problems on upper triangular matrices Linear and Multilinear Algebra 1998 45 2-3 189 206 MR1671619 2-s2.0-0000541014 10.1080/03081089808818586 Beidar K. I. Brešar M. Chebotar M. A. Jordan isomorphisms of triangular matrix algebras over a connected commutative ring Linear Algebra and Its Applications 2000 312 1–3 197 201 10.1016/s0024-3795(00)00087-2 MR1759333 Zhang J. H. Jordan isomorphisms of nest algebras Acta Mathematica Sinica 2002 45 4 819 824 MR1925327 Lu F. Jordan isomorphisms of nest algebras Proceedings of the American Mathematical Society 2003 131 1 147 154 10.1090/s0002-9939-02-06587-5 MR1929034 Chebotar M. A. Ke W.-F. Lee P.-H. Wong N.-C. Mappings preserving zero products Studia Mathematica 2003 155 1 77 94 10.4064/sm155-1-6 MR1961162 2-s2.0-0037698821 Hou J. Jiao M. Additive maps preserving Jordan zero-products on nest algebras Linear Algebra and its Applications 2008 429 1 190 208 10.1016/j.laa.2008.02.021 MR2419149 2-s2.0-42749095668 Zhang J.-H. Yang A.-L. Pan F.-F. Linear maps preserving zero products on nest subalgebras of von Neumann algebras Linear Algebra and Its Applications 2006 412 2-3 348 361 10.1016/j.laa.2005.07.001 MR2182966 2-s2.0-27944482950 Xu X. Simple conformal algebras generated by Jordan algebras http://arxiv.org/abs/math/0008224 Günaydin M. Extended superconformal symmetry, Freudenthal triple systems and gauged WZW models Strings and Symmetries 1995 447 Berlin, Germany Springer 54 69 Lecture Notes in Physics 10.1007/3-540-59163-x_255 MR1356233 Ramond P. Algebraic dreams http://arxiv.org/abs/hep-th/0112261 Mickelsson J. Gerbes, (twisted) K-theory, and the supersymmetric WZW model http://arxiv.org/abs/hep-th/0206139 Gauntlett J. P. Gibbons G. W. Hull C. M. Townsend P. K. BPS states of D = 4 N = 1 supersymmetry Communications in Mathematical Physics 2001 216 2 431 459 10.1007/s002200000341 Gilfeather F. Larson D. R. Nest-subalgebras of von Neumann algebras Advances in Mathematics 1982 46 2 171 199 10.1016/0001-8708(82)90022-6 MR679907 2-s2.0-0000038135 Davidson K. R. Nest Algebras 1988 191 Longman Scientific & Technical Pitman Research Notes in Mathematics MR972978